Research on the Investment Strategy Based on Option Volatility Smiles - Bao, Ruoyu (BCP Business & Management, 2022)
Under the Black-Scholes efficient market assumptions, the implied volatility of options should be constant when the option value state and the remaining maturity period change. However, in the real world, the implied volatility of options in different value states will show smile pattern with given remaining maturity period. Numerous empirical studies have found that implied volatility smile slopes have significant predictive function for stock market returns. Based on this, this paper selects the historical trading data of SSE 50 ETF options to verify the existence of option volatility smile in Chinese capital market. And uses the tilt degree of implied volatility as a stock risk premium factor to select stocks, as to obtain a portfolio with excess returns. This paper portrays the morphological characteristics of option implied volatility, as well as confirms the existence of option volatility smile in Chinese capital market. In addition, this paper demonstrates that the tilt of the smile has significant predictive function for the underlying market trend. Finally, this paper constructs an investment strategy using the tilt degree of the implied volatility smile as an indicator. The findings of this study will help investors to select stocks and construct portfolios based on implied volatility in order to obtain higher returns.